Enhancing Transaction Smoothness with QRIS Technology: The Role of DIGI by Bank BJB in Optimizing Customer Experience at the Banjar Branch - Faizal, Riza; Marlina, Lina; Setiawan, Ati S (Brilliance: Research of Artificial Intelligence, 2024)
The implementation of the Quick Response Code Indonesian Standard (QRIS) in the DIGI by bank bjb application faces challenges in enhancing the transaction flow for customers at the Banjar Branch. The primary issue is the demand for ease, speed, and efficiency in digital transactions, while aspects such as promotions and QRIS scanning capability across various merchants remain suboptimal. This study aims to examine the impact of QRIS usage within the DIGI application on the transaction flow for bank bjb customers. A quantitative research method with an explanatory survey approach was employed, involving 100 respondents who are bank bjb customers in the Banjar area. Data was collected using a Likert-scale questionnaire and analyzed using simple linear regression. The results indicate a significant positive influence of QRIS usage on transaction flow, with a t-value that demonstrates a strong correlation. The average customer satisfaction score indicated a “Very Good” criterion. These findings imply that the QRIS feature in the DIGI by bank bjb application can enhance customer transaction experiences; however, the bank needs to improve promotional features and expand QRIS scanning capabilities to further increase customer satisfaction and the competitiveness of its digital services.